Al-Ittijâh Al-‘Ilmy fi Tafsîr Al-Imâm Al-Alûsy Rûh Al-Ma’âny - Haikal Mustafti (Studia Quranika, 2018)
This article examines the relevance of scientific of tafseer in Rûh al-Ma'âny, by Imam al-Alusy. Al-Alusy in his Tafseer tried to interpret the verse that has relevance with nature, he discussed deeply in it. Al-Alusy tries to discuss the Qur'anic verses in his tafseer, so that it can be found ‘ilmi pattern, as found in the Surah al-A'raf verse 31 (health sciences), the Surah al-Mu'minun verses 12-14, the Surah az-Zumar verse 6 (gynecology), the Surah Yasin verse 38 (natural science), and the Surah al-Hijr verse 22 (plant science). Besides being known by Sufi approach in his tafseer, he has qualified the acceptance of tafsee with ‘ilmi pattern, although his tafseer is more dominated by tafseer of the Qur'an with the hadits of the Prophet related to the verses of scientific verse, due to fear of mistakes in interpreting the Qur'an.